(3GOGQI GdJShjb (B:s (3GdeaGgje (B-(3GdGSJQGJjLjGJ (B-(3GdJWHjbGJ (B/s - (3LHQ, CMeOs ((3GdbGgQI(B: s (3GdecJHI GdYUQjI ddfTQ hGdJhRjY(B, s, 2007)
(3GdHjFI GdJShjbjI ,GdYedGA hGSJQGJjLjGJ GdShb,GdESJQGJjLjGJ GdJShjbjI,GdJNWjW hGdQbGHIs
(3HHdhZQGajG(B:(3U(B.469-472s
Keywords: (3EOGQI GdJShjbs